if h(x)=x-7 and g(x)=x^ which expression is equivalent to (g•h)(5)?

A) (5-7)^
B) (5)^-7
C) (5)^ (5-7)
D) (5-7)x^

Respuesta :

Assuming that by ^, you mean ², here's how you do this:
(g•h)(5) means that you need to solve g(h(5)). So, you plug 5 in for x in h(x), then you plug the solution of that in for x in g(x) like so:
[tex]h(5)=5-7 \\ g(h(5))= (5-7)^{2} [/tex]

The answer is A. (5-7)
²

Hope this helps!

Answer:

A (5-7)^

Step-by-step explanation:

We have the next two functions h(x)=x-7 and g(x)=x^. We need to find (g•h) that is equal to g(h(x)) then:

(g•h)=g(h(x))=(x-7)^

Finally in the poin x=5 we have:

(g•h)=g(h(x))=(x-7)^

(g•h)=g(h(5))=(5-7)^

Then the answer is A